MANFAAT PUASA BAGI KESEHATAN TUBUH MENURUT PERSPEKTIF ISLAM DAN KESEHATAN - Mumtazza, Hazel; Ahsan, Aflina Asfahani; Chaniago, Faathir Muhammad; Muzakkir, Muhammad Ridho; Anwar, Saepul (JURNAL KAJIAN ISLAM MODERN, 2025)
Fasting is an obligatory act of worship for Muslims that not only has spiritual value but also has various benefits for physical and mental health. This study examines the benefits of fasting from an Islamic and health perspective, using a qualitative approach. We collected data through a literature review and in-depth interviews with religious and health experts. The results showed that fasting can improve physical health by regulating diet, resting the digestive system, and improving metabolism. In terms of mental health, fasting strengthens mental resilience, improves self-control, and reduces stress, which has a positive impact on emotional and spiritual balance. These benefits not only include the prevention of diseases such as obesity, diabetes, and digestive disorders but also include holistic improvements in quality of life. Researchers should investigate the advantages of fasting on days other than Ramadan, like Monday-Thursday fasting or Davidic fasting. This may provide additional insight into the effects of fasting over the long term and different routines.